Measurement of the prompt D0 nuclear modification factor in p-Pb collisions at √sNN=8.16 TeV - Aaij, Roel; Bachmann, Sebastian; Borsato, Martino; Caspary, Rowina; Frau, Giulia; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; Kubat, Jakub; Leverington, Blake; Marks, Jörg; et al. (Physical review letters, 2023)
The production of prompt D0 mesons in proton-lead collisions in both the forward and backward rapidity regions at a center-of-mass energy per nucleon pair of √sNN=8.16 TeV is measured by the LHCb experiment. The nuclear modification factor of prompt D0 mesons is determined as a function of the transverse momentum pT, and the rapidity in the nucleon-nucleon center-of-mass frame y∗. In the forward rapidity region, significantly suppressed production with respect to pp collisions is measured, which provides significant constraints on models of nuclear parton distributions and hadron production down to the very low Bjorken-x region of ∼10−5. In the backward rapidity region, a suppression with a significance of 2.0-3.8 standard deviations compared to parton distribution functions in a nuclear environment expectations is found in the kinematic region of pT>6 GeV/c and −3.25<y∗<−2.5, corresponding to x∼0.01.
Im Titel ist "0" hochgestellt und "NN" tiefgestellt
LHCb Collaboration: R. Aaij, S. Bachmann, M. Borsato, R. Caspary, G. Frau, P.A. Günther, X. Han, S. Hansmann-Menzemer, J. Hu, J. Kubat, B. Leverington, J. Marks, R. Skuza, D. Unverzagt, U. Uwer, C. Wang, L. Witola, A. Zhelezov [und 997 weitere]
Gesehen am 16.02.2024